Queen of the sea - Meconis, Dylan (Old Saybrook, Connecticut : www.micromarketing.org, 2019)
"Cult graphic novelist Dylan Meconis offers a rich reimagining of history in this beautifully detailed hybrid novel loosely based on the exile of Queen Elizabeth I by her sister, Queen Mary. When her sister seizes the throne, Queen Eleanor of Albion is banished to a tiny island off the coast of her kingdom, where the nuns of the convent spend their days peacefully praying, sewing, and gardening. But the island is also home to Margaret, a mysterious young orphan girl whose life is upturned when the cold, regal stranger arrives. As Margaret grows closer to Eleanor, she grapples with the revelation of the island's sinister true purpose as well as the truth of her own past. When Eleanor's life is threatened, Margaret is faced with a perilous choice between helping Eleanor and protecting herself. In a hybrid novel of fictionalized history, Dylan Meconis paints Margaret's world in soft greens, grays, and reds, transporting readers to a quiet, windswept island at the heart of a treasonous royal plot."--
[Typographic symbols and accents removed for systems compatibility.]
Title and description based on researched data; resource not viewed.
Keywords: Tudor, House of -- Comic books, strips, etc; Monarchy -- Great Britain -- History -- 16th century -- Comic books, strips, etc; Great Britain -- History -- Tudors, 1485-1603 -- Comic books, strips, etc; Great Britain -- Politics and government -- 1485-1603 -- Comic books, strips, etc; Graphic novels; Comics (Graphic works)